1998
DOI: 10.1007/s002800050809
|View full text |Cite
|
Sign up to set email alerts
|

Doxorubicin pharmacokinetics: the effect of abnormal liver biochemistry tests

Abstract: We studied variability in doxorubicin pharmacokinetics in 24 patients with abnormal liver biochemistry tests. Blood samples were collected after the first cycle of single-agent doxorubicin given as an i.v. bolus and plasma levels were measured by high-performance liquid chromatography. The relationship between doxorubicin clearance (dose/AUC) and liver biochemistry tests (AST, bilirubin, albumin, alkaline phosphatase and indocyanine green clearance) was investigated. Patients with a raised bilirubin level had … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(8 citation statements)
references
References 15 publications
0
7
0
1
Order By: Relevance
“…20, 21 However, the therapeutic efficacy of this relatively insoluble small-molecule drug is limited by its low bioavailability and short-plasma half-life, necessitating frequent dosing. 22 In addition, the often life-threatening side effects (cardiotoxicity, 23 bone marrow suppression, 24, 25 infertility, 26 etc.) that accompany the use of doxorubicin, including latent development of leukemia after prolonged treatment, 27 deem this an undesirable chemotherapeutic agent.…”
Section: Resultsmentioning
confidence: 99%
“…20, 21 However, the therapeutic efficacy of this relatively insoluble small-molecule drug is limited by its low bioavailability and short-plasma half-life, necessitating frequent dosing. 22 In addition, the often life-threatening side effects (cardiotoxicity, 23 bone marrow suppression, 24, 25 infertility, 26 etc.) that accompany the use of doxorubicin, including latent development of leukemia after prolonged treatment, 27 deem this an undesirable chemotherapeutic agent.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, in this study, a negative correlation between Alb and AUC/D of DXR was found in elderly patients. It has been reported that DXR clearance (CL) correlates with various liver function test values, including Alb 25,26 . DXR is eliminated primarily by hepatic metabolism and biliary excretion.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the present study might have missed possible influence of xenograft tumors, similar to other diseases or disease statuses ( Li et al, 2019 ), as well as sex ( Franconi and Campesi, 2014 ) on the PK properties of Dox or Sor (e.g., volume of the central compartment), whereas the differences in PK among mouse strains seem minimal ( Barr et al, 2020 ). Indeed, it has been reported that doxorubicin clearance was relatively higher in men ( n = 6) than in women ( n = 21) (59 vs. 27 l•h −1 •m −2 ) ( Dobbs et al, 1995 ), and abnormal liver functions tended to correlate with lower levels of doxorubicin clearance ( Twelves et al, 1998 ). Baseline body weight was identified as a statistically significant covariate for variable sorafenib distributional volume among patients with solid tumors ( Jain et al, 2011 ), whereas no association was found between organ function and systemic sorafenib exposure, including patients with severe liver and kidney impairment ( Miller et al, 2009 ).…”
Section: Discussionmentioning
confidence: 99%